PEMBELAJARAN MATEMATIKA BERBASIS MASALAH - Kiki Herdiansyah (Universitas Muhammadiyah Kotabumi, 2019)
The purpose of mathematics learning is the student will have high order thinking. This will be needed by student to solve their problems. Learning approach like teacher centered study can not develop their high order thinking. High order thinking is a thinking-level involve bloom's taxonomics. One of the student-centered learning is problem based learning. It can develop a high order thinking in mathematics. This article will show up to you about the problem-based mathematics learning.